PENGARUH PRODUKTIVITAS KERJA KARYAWAN TERHADAP PENGELOLAAN KEARSIPAN DI PT. PELABUHAN INDONESIA II (Persero) CABANG PELABUHAN BENGKULU PULAU BAAI - ARDA TULZANA; EVI LORITA; HARIUS EKO SAPUTRA (Professional: Jurnal Komunikasi dan Administrasi Publik, 2021)
This study aims to determine the influence of employee work productivity on archival management at PT. Pelabuhan Indonesia II (Persero) Bengkulu Branch Baai Island. The subjects of this study were the employees at PT. Pelabuhan Indonesia II(Persero) Bengkulu Branch Pulau Baai, with a total of 62 employees through 16 questionnaires. The form of this research his associative research with quantitative analysis, with the intention to find the influence between the independent variables and the dependent variable. Data analysis techniques used in this research is a quantitative technique to test the relationship / influence between independent variables and dependent variables using statistical calculations, namely product moment correlation, determination test, and T-test. he results of product moment correlation analysis show r-count>rtableis=0.454>(Rtable)= 0.254, which means there is a correlation between the two variables, at the level of the moderate correlation 0.40-0.599, while the direction of the correlation is positive because the value of Rispositive. The Coefficient of Determination Test Results (R²) can be obtained (0≤0.206≤1), which means that the correlation between employee work productivity to wards archival management has alow influence of 20.6%. The results of the T-test show that the value of countis 3.922, sot-count>ttable is 3.922>1.670, the employee work productivity variable has a positive and sign if i can’t influence on the management of archives at PT. Pelabuhan Indonesia II (Persero) Bengkulu Branch.